Cogging Torque Reduction Technique on E-Core Hybrid Flux Switching Motor by Notching and Pole Pairing - Jaudah Abd Rani; Erwan Sulaiman; Md Zarafi Ahmad; Mohd Fairoz Omar; Chockalingam Aravind Vaithilingam (Institute of Advanced Engineering and Science, 2018)
In the past, 4S-10P E-Core Hybrid Flux Switching Motor (HFSM) had been studied. However, the motor suffers high cogging torque but it has high performance in terms of high power and high torque at high speed. Therefore, this paper is proposing the cogging torque reduction techniques to minimize the cogging torque. The high cogging torque gave an undesirable effect during low operating speed of the motor. In order to tackle the issue, the cogging torque mechanism in equation is laid out as a form of reference. Then the reduction techniques employed on the designs and analyzed with Finite Element analysis (FEA) in JMAG. The results show the cogging torque of the optimized design is 44.45% of the motor torque. Besides, the techniques employed to identify which techniques gave the most cogging torque reduction and analyzed the geometrical difference using the cogging torque mechanism. Finally, the analysis is discussed based on the modified geometrics.